2011
DOI: 10.19153/cleiej.14.3.1
|View full text |Cite
|
Sign up to set email alerts
|

The EasySOC Project: A Rich Catalog of Best Practices for Developing Web Service Applications∗

Abstract: The Service-Oriented Computing (SOC) paradigm has gained a lot of attention in the software in- dustry since SOC represents a novel way of architecting distributed applications. SOC is mostly materialized via Web Services, which allow developers to expose their application as building blocks for other applications by defining a clear and public interface. Although conceptually and technologically mature, SOC still lacks adequate development support from a methodological point of view. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For instance, in Rodriguez et al (2010a), the authors state that "There is no silver bullet to guarantee that potential consumers of a Web Service will effectively discover, understand and access it. However, we have empirically shown that a WSDL document can be improved to simultaneously address these issues by following six steps.…”
Section: Approaches To Remove Wsdl Discoverability Anti-patternsmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, in Rodriguez et al (2010a), the authors state that "There is no silver bullet to guarantee that potential consumers of a Web Service will effectively discover, understand and access it. However, we have empirically shown that a WSDL document can be improved to simultaneously address these issues by following six steps.…”
Section: Approaches To Remove Wsdl Discoverability Anti-patternsmentioning
confidence: 99%
“…The work of Rodriguez et al (2010d) presents the catalogue of WSDL discoverability anti-patterns, while in Rodriguez et al (2010a) the authors introduce guidelines to remedy the anti-patterns. Such guidelines are based on refactoring actions for WSDL documents.…”
Section: Approaches To Remove Wsdl Discoverability Anti-patternsmentioning
confidence: 99%
See 2 more Smart Citations